Penerapan Metode Double Exponential Smoothing Brown Untuk Peramalan Indeks Pembangunan Manusia (IPM) Kabupaten Belitung Tahun 2023-2027: Application of Double Exponential Smoothing Brown Method for Forecasting Human Development Index (HDI) of Belitung Regency in 2023-2027 - Syarmilati, Tasyah; Rifai, Nur Azizah Komara (Journal of Applied Islamic Economics and Finance, 2024)
The Belitung Regency Government aims to improve the quality of life of a just society, and the leading performance indicator is the Human Development Index. Therefore, the author wants to see a picture of the progress of aspects of the lives of the people of Belitung Regency by looking at the estimated value of the Human Development Index for the following five periods, especially from 2023 to 2027 using Human Development Index (HDI) data using the Double Exponential Smoothing Brown method. Based on the research that has been conducted, the author can conclude that the value of the Human Development Index (HDI) of Belitung Regency from 2023 to 2027 tends to have an increasing HDI value of 73.81, 74.29, 74.77, 75.25 and 75.73 respectively.